Analisis Pengaruh Brand Image, Persepsi Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Vans Indonesia - Andika Yanutri Pambudi; Wiyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of brand image, price perception, promotion, and product quality on product purchasing decisions vans indonesia. This study is included in the category of survey research using questionnaires as a primary data collection tool. The population in this study is all FEB UMS students who have made purchases and who have used Vans Indonesia products. The sampling technique used in this study is purposive sampling. The results can be concluded that partially brand image and product quality does not significantly affect the purchase decision, while the perception of price and promotion have a positive and significant effect on the purchase decision